Atomic force microscopy-based force measurements on animal cells and tissues - Gautier, Helene O. B.; Thompson, Amelia J.; Achouri, Sarra; Koser, David E.; Holtzmann, Kathrin; Moeendarbary, Emad; Franze, Kristian (Methods in Cell Biology, 2015)
During development, normal functioning, as well as in certain pathological conditions, cells are influenced not only by biochemical but also by mechanical signals. Over the past two decades, atomic force microscopy (AFM) has become one of the key tools to investigate the mechanical properties and interactions of biological samples. AFM studies have provided important insights into the role of mechanical signaling in different biological processes. In this chapter, we introduce different applications of AFM-based force measurements, from experimental setup and sample preparation to data acquisition and analysis, with a special focus on nervous system mechanics. Combined with other microscopy techniques, AFM is a powerful tool to reveal novel information about molecular, cell, and tissue mechanics.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Adhesion; AFM; Biomechanics; Elastic modulus; Elasticity; Scanning force microscopy; SFM; Stiffness